NATURAL COURSE OF CHRONIC VIRAL HEPATITIS B AND C IN CHILDREN - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Isomadinova Lola Kamoliddinovna; Pardayeva Shahlo Abriy Qizi (TADQIQOTLAR.UZ, 2024)
Annotation. Chronic viral hepatitis is a pressing problem in modern healthcare, due to the almost universal spread of this infection and the high risk of developing unfavorable outcomes. The most difficult group is represented by patients with mixed hepatitis,  which  is  associated  with  more  rapid  progression  of  the  disease  and  the development of liver cirrhosis. The article presents data from long-term observation of children with chronic hepatitis B+C (CHB+C), demonstrates the features of the clinical course,  the  nature  of  biochemical,  immunological,  morphological  changes  in  the natural course of the disease.